Characterization of the molten globule state of retinol-binding protein using a molecular dynamics simulation approach. - Paci, E; Greene, L; Jones, R; Smith, L (2005)
Retinol-binding protein transports retinol, and circulates in the plasma as a macromolecular complex with the protein transthyretin. Under acidic conditions retinol-binding protein undergoes a transition to the molten globule state, and releases the bound retinol ligand. A biased molecular dynamics simulation method has been used to generate models for the ensemble of conformers populated within this molten globule state. Simulation conformers, with a radius of gyration at least 1.1 A greater than that of the native state, contain on average 37%beta-sheet secondary structure. In these conformers the central regions of the two orthogonal beta-sheets that make up the beta-barrel in the native protein are highly persistent. However, there are sizable fluctuations for residues in the outer regions of the beta-sheets, and large variations in side chain packing even in the protein core. Significant conformational changes are seen in the simulation conformers for residues 85-104 (beta-strands E and F and the E-F loop). These changes give an opening of the retinol-binding site. Comparisons with experimental data suggest that the unfolding in this region may provide a mechanism by which the complex of retinol-binding protein and transthyretin dissociates, and retinol is released at the cell surface.